Real-space observation of ultraconfined in-plane anisotropic acoustic terahertz plasmon polaritons - Chen, S; Leng, P L; Konečná, A; Modin, E; Gutierrez-Amigo, M; Vicentini, E; Martín-García, B; Barra-Burillo, M; Niehues, I; Maciel Escudero, C; Xie, X Y; Hueso, L E; et al. (Nature materials, 2023)
Thin layers of in-plane anisotropic materials can support ultraconfined polaritons, whose wavelengths depend on the propagation direction. Such polaritons hold potential for the exploration of fundamental material properties and the development of novel nanophotonic devices. However, the real-space observation of ultraconfined in-plane anisotropic plasmon polaritons (PPs)-which exist in much broader spectral ranges than phonon polaritons-has been elusive. Here we apply terahertz nanoscopy to image in-plane anisotropic low-energy PPs in monoclinic Ag2Te platelets. The hybridization of the PPs with their mirror image-by placing the platelets above a Au layer-increases the direction-dependent relative polariton propagation length and the directional polariton confinement. This allows for verifying a linear dispersion and elliptical isofrequency contour in momentum space, revealing in-plane anisotropic acoustic terahertz PPs. Our work shows high-symmetry (elliptical) polaritons on low-symmetry (monoclinic) crystals and demonstrates the use of terahertz PPs for local measurements of anisotropic charge carrier masses and damping.
Keywords: Blood Platelets; trombocyty; Anisotropy; molekulová hmotnost; Molecular Weight; Acoustics; akustika; anizotropie